Efficacy of aspergillus sp. for degradation of chlorpyrifos in batch and continuous aerated packed bed bioreactors - Yadav M.; Srivastva N.; Shukla A.K.; Singh R.S.; Upadhyay S.N.; Dubey S.K. (My University, 2025)
Aerobic biodegradation of chlorpyrifos (CP) by Aspergillus sp. was investigated in batch and continuous packed bed bioreactors. The optimal process parameters for achieving the maximum removal efficiency (RE), determined using a batch bioreactor packed with polyurethane foam pieces, were inoculum level: 2.5 mg (wet weight) mL−1, pH 7.0, temperature 28 °C, DO 5.8 mg L−1, and CP concentration 300 mg L−1. The continuous packed bed bioreactor was operated at flow rates ranging from 10 to 40 mL h−1 while keeping other parameters at their optimal level. Steady-state CP removal efficiencies greater than 85 % were obtained up to the inlet loading of 180 mg L−1 d−1. The continuous bioreactor behaved as a plug flow unit and was able to stabilize quickly after perturbation in the inlet loading. © 2014, Springer Science+Business Media New York.